Cryopreservation of isolated mouse germinal vesicles - Kren, Radomir; Fulka, Josef; Fulka, Helena (The Journal of reproduction and development, 2005)
The storage of unfertilized oocytes, either immature, maturing or mature, is still unsatisfactory. Here we describe an approach in which germinal vesicles isolated as karyoplasts from immature oocytes are vitrified by open the pulled straws (OPS) method in evacuated porcine zonae pellucidae. After thawing, their survival was almost absolute. Moreover, when thawed GV-karyoplasts were fused to immature oocyte cytoplasts the maturation of reconstructed cells resulted in the production of secondary oocytes--metaphase II.
Keywords: Cell Survival; kryoprezervace; Cryopreservation; fertilizace in vitro; Female; viabilita buněk; Zona Pellucida; zvířata; myši; Fertilization in Vitro; Mice; oocyty; Swine; Mice, Inbred ICR; ženské pohlaví; zona pellucida; Animals; myši inbrední ICR; Oocytes; prasata